Development of Earthquake-proof Fittings of Traditional Wooden Frame Structures - Takehiro Wakita; Fuyuki Konuta; Akihisa Kitamori; Yasuo Kataoka (Masyarakat Peneliti Kayu Indonesia, 2011)
There are many old traditional wooden frame buildings which were specified as cultural heritage or will be specified as Japanese important building in the near future. But there are many buildings which do not have good performance against seismic action. The purpose of the investigation is to develop the earthquake proof fittings, and to apply them to the traditional wooden structures. In concrete terms, the types of the earthquake-proof fittings are the Kamachi door, the acrylic door and the hinged wooden door. Strength and rigidity of the earthquake proof fittings were estimated experimentally, and they were applied to reinforce the two old Buddhist temples.